Quantitative palynological analysis of Julian clastic rocks from the lead-zinc deposit of Mežica - Jelen, Bogomir; Kušej, Janko (Geologija, 1982)
The calcareous-dolomitic sequence of the Karnian at Mežica is interbedded with three horizons of clastic rocks. Through the palynological assemblages of the 1st horizon a deltaic environment is reflected; spores of pteridophytes being abundant. An ammonoid biocoenose, reported from this horizon previously, may possibly not be autochthonous. The 2nd horizon is characterized by the spores of mangrove trees. In the 3rd horizon xerophytic elements prevail. By the frequency distribution of spores, pollen, and acritarchs a decreasing deltaic influence and an ever increasing marine influence is indicated from the 1st through the 2nd to the third horizon. By the combination Camerosporites secatus and Ovalipollis pseudoalatus the northern belt of the equatorial Karnian palynofloristic domain is recognized.